2019
DOI: 10.35249/rche.45.4.19.27
|View full text |Cite
|
Sign up to set email alerts
|

Andromorphic Crocothemis servilia (Drury) (Odonata: Libellulidae): new records from India

Abstract: Revista Chilena de Entomología (2019) 45 (4): 699-703. Este es un artículo de acceso abierto distribuido bajo los términos de la licencia Creative Commons License (CC BY NC 4.0) Scientific Note Andromorphic Crocothemis servilia (Drury) (Odonata: Libellulidae): new records from India Odonato andromórfico Crocothemis servilia (Drury) (Odonata: Libellulidae): nuevos registros de la India Abstract. Six new records of andromorphic Crocothemis servilia from Eastern India are described here. Detail comparisons of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…Joshi & Agashe (2020) showed that colour variation could be related to genetic polymorphism and ontogenic change where an immature Agriocnemis pygmaea (Rambur, 1842) was observed to be heteromorphic but acquired andromorphic colours on reaching sexual maturity. In European Zygoptera, andromorphs have been reported in 54 % of genera ( Cordero & AndrÉs 1996) but they are rare in Anisoptera, and most occur in libellulid genera such as Crocothemis, Neurothemis, Sympetrum, and Urothemis ( Kumar 1988; Kotarac 1996; Corbet 1999; Payra 2019a, 2019b; Willink et al 2019; Joshi et al 2020; Prasad et al 2000; Andrew 2013). Additionally, among aeshnids, four studies of androchrome females from the Palaearctic region have been made on Aeshna grandis (Linnaeus, 1758) , Anax guttatus (Burmeister, 1839) , A. immaculifrons Rambur, 1842, and A. imperator Leach in Brewster, 1815 ( Fincke et al 2005) .…”
Section: Introductionmentioning
confidence: 99%
“…Joshi & Agashe (2020) showed that colour variation could be related to genetic polymorphism and ontogenic change where an immature Agriocnemis pygmaea (Rambur, 1842) was observed to be heteromorphic but acquired andromorphic colours on reaching sexual maturity. In European Zygoptera, andromorphs have been reported in 54 % of genera ( Cordero & AndrÉs 1996) but they are rare in Anisoptera, and most occur in libellulid genera such as Crocothemis, Neurothemis, Sympetrum, and Urothemis ( Kumar 1988; Kotarac 1996; Corbet 1999; Payra 2019a, 2019b; Willink et al 2019; Joshi et al 2020; Prasad et al 2000; Andrew 2013). Additionally, among aeshnids, four studies of androchrome females from the Palaearctic region have been made on Aeshna grandis (Linnaeus, 1758) , Anax guttatus (Burmeister, 1839) , A. immaculifrons Rambur, 1842, and A. imperator Leach in Brewster, 1815 ( Fincke et al 2005) .…”
Section: Introductionmentioning
confidence: 99%